Qualitative Assessment of Basel III Liquidity Standards and its Application in the UAE - Kapur, Manoj; Banerjee, Arindam; Malik, Kunjana (Indian Journal of Finance and Banking, 2020)
The Basel Committee for Banking and Supervision (BCBS) introduced two key liquidity ratios to strengthen the short- and long-term liquidity positions of the banks around the globe. These ratios were designed to achieve two key distinct objectives. Firstly, to encourage banks' short-term resilience to the liquidity risks by ensuring there are sufficient high-quality liquid assets to survive a significant stress which may last for 30 days. Calculation of this ratio is called as Liquidity Coverage Ratio (LCR). Secondly, to promote bank resilience over a longer time horizon, at least annually, by creating additional incentives for banks to fund their activities with more stable sources of funding. This led to creation of Net Stable Funding Ratio (NSFR). While these structural ratios are mostly quantitative, the underlying factors that are needed to calculate these ratios include qualitative factors as well. The paper analyzed the implementation of Basel III standards for the banking sector in the UAE. In particular, the timelines specified by the Central bank of the UAE and its implementation by the Domestic-Systemically Important Banks (D-SIBs) in the UAE was tracked by this paper. The study found a disconnect between the disclosure requirements by Basel III and disclosure made in the published annual financial statements of the banks. The study also discussed the extent of disclosures made by the D-SIBs and how relevant disclosures may improve the transparency of the liquidity risk management of the bank.JEL Classification Codes: E58, G32, G38.